Intraseasonal characterization of glass eel migration in the River Tiber: Space and time dynamics - CICCOTTI, ELEONORA; SCARDI, MICHELE; FRESI, EUGENIO; CATAUDELLA, STEFANO; Ricci, T (Journal of Fish Biology, 1995)
Glass eel (Anguilla anguilla) upstream migration was studied in the River Tiber estuary to obtain a better understanding of spatial and temporal migration dynamics within the season of ascent. Using data from glass eel fisheries, time series analysis of daily catches per unit of effort revealed a fortnightly cycle that can be related to invasion waves possibly corresponding to tidal currents. The amplitude of these waves appeared to correspond to the tidal area of the estuary. Furthermore, glass eels apparently had a delay in this area before resuming upstream migration. (C) 1995 The Fisheries Society of the British Isles